Analysis of the geomechanical behavior of the rock mass in gallery level 4040, Victoria mine - Catalan-Mendoza, David Francisco (2023)
The trend in countries with experience in mining exploitation is to have safe practices to conserve their most valuable resource, their personnel; For this reason, we set ourselves the objective of determining the geomechanical behavior of the rock mass analyzed through geomechanical classifications gallery level 4040 in the Victoria mine, Andahuaylas 2021; The study is of applied type, level; descriptive – explanatory. The results were obtained by applying computer programs such as Roclab, Dips and Phases; the RMR value (corrected) is 48, which qualifies as regular; which means that in excavation such as pilot cut and benching with 1.5 to 3 m of advance in the pilot cut, the rock bolts must be systematic bolts of 4 m, 1.5-2 m spacing on the ceiling and walls with welded mesh; the concrete thrown from 50 to 100 mm on the roof and 30 mm on the sides. The investigation concludes that in slope areas in structural domain (D.E) 1 there is no risk since there are no poles, in D.E 4 there is a concentration of poles therefore the possibility of landslide. In tunnel structures in D.E 2 there is no overturning or overturning, in D.E 3 and 5 there are wedges since in the first case shotcrete must be applied, and for the second case a thin layer of shotcrete must be applied.